Metabolic syndrome: epidemiology, mechanisms, and current therapeutic approaches - Hamooya, Benson M.; Siame, Lukundo; Muchaili, Lweendo; Masenga, Sepiso K.; Kirabo, Annet (Frontiers in Nutrition, 2025)
Metabolic syndrome (MetS) is a complex condition marked by central obesity, dyslipidemia, hypertension, insulin resistance, oxidative stress, and chronic inflammation. These risk factors significantly raise the risk of cardiovascular disease (CVD) through various mechanisms, leading to a public health challenge. MetS contributes to CVD through cardiometabolic derangements such as endothelial dysfunction, atherosclerosis, oxidative stress, and inflammation. Dyslipidemia, especially elevated triglycerides and reduced high-density lipo-protein (HDL) cholesterol is central to atherosclerosis. Additionally, hypertension and insulin resistance damage blood vessels, a process exacerbated by chronic inflammation and oxidative stress. Thus, managing MetS and its components through lifestyle changes like weight control, dietary improvements, exercise, and smoking cessation is essential for reducing CVD risk. Medications targeting specific risk factors, such as blood sugar, cholesterol, and blood pressure, may also be required. Raising awareness and early screening are crucial to countering MetS’s impact on public health. This review provides a comprehensive overview of the mechanisms by which MetS contributes to CVD and the intricate interplay of factors and molecular pathways linking MetS to CVD.